Design Analysis to Enhance Financial Education for Student Entrepreneurs in University - Aldilla Iradianty; Palti Marulitua Sitorus (Asia Pacific Journal of Management and Education (APJME), 2024)
Telkom University organizes an entrepreneurship program that serves entire students who want to start a business with a selection method to be incubated for one semester or more. Doing business for Student Entrepreneurship (SE) requires financial management expertise because it is very important to ensure that products are in line with expectations and efficient use of resources to maximize business profits. Financial skills are also important in running businesses. From that, the university holds learning finance management in the process of business incubation, but SE feels learning financial management is not interesting. Therefore, this research aims to discuss the needs of financial management for SE, lecturers, and universities with a qualitative approach through focus group discussion. The study's key findings are that SE needs to learn about financial statements. They also expect this to be done automatically on a digital basis that is easy to use, so entrepreneurial students can take advantage of the automatically generated data for proper decision-making and can focus on the creative and innovative aspects of the product. Financial apps for financial statements could potentially be made by digital software developers.